Characterization of olfactory sensory neurons in the striped ambrosia beetle Trypodendron lineatum - Biswas, Twinkle; Yuvaraj, Jothi Kumar; Hansson, Bill S.; Löfstedt, Christer; Anderbrant, Olle; Andersson, Martin N. (Frontiers in Physiology, 2023)
The striped ambrosia beetle Trypodendron lineatum (Coleoptera, Curculionidae, Scolytinae) is a major forest pest in the Holarctic region. It uses an aggregation pheromone and host and non-host volatiles to locate suitable host trees, primarily stressed or dying conifer trees. The beetles bore into the xylem and inoculate spores of their obligate fungal mutualist Phialophoropsis ferruginea inside their excavated egg galleries, with the fungus serving as the main food source for the developing larvae. Olfactory sensory neuron (OSN) responses to pheromones and host volatiles are poorly understood in T. lineatum and other ambrosia beetles, and nothing is known about potential responses to fungal volatiles. Hence, we screened responses of OSNs present in 170 antennal olfactory sensilla using single sensillum recordings (SSR) and 57 odor stimuli, including pheromones, host and non-host compounds, as well as volatiles produced by P. ferruginea and fungal symbionts of other scolytine beetles. Thirteen OSN classes were characterized based on their characteristic response profiles. An OSN class responding to the aggregation pheromone lineatin was clearly the most abundant on the antennae. In addition, four OSN classes responded specifically to volatile compounds originating from the obligate fungal mutualist and three responded to non-host plant volatiles. Our data also show that T. lineatum has OSN classes tuned to pheromones of other bark beetles. Several OSN classes showed similar response profiles to those previously described in the sympatric bark beetle Ips typographus, which may reflect their shared ancestry.